2020
DOI: 10.32014/2020.2518-1491.105
|View full text |Cite
|
Sign up to set email alerts
|

Prospects for the Integrated Use of Slag Wastes From Ferrochrome Production for Heat-Resistant Materials

Abstract: The research results of physicochemical and physicotechnical properties of slag wastes from ferrochrome production as raw materials for heat-resistant materials are presented. Chemical and mineralogical composition of slag from high-carbon ferrochrome production and slag from low-carbon ferrochrome production, as well as their constituent main crystalline phases, represented by magnesium and calcium aluminosilicates of complex composition, have been determined by physicochemical research methods. According to … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
1
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 0 publications
0
1
0
Order By: Relevance
“…In the slag from the production of low-carbon ferrochrome, the main crystalline phase is calcium orthosilicateγ-Ca2SiO4, as well as magnesium orthosilicate (forsterite) Mg2SiO4 [85]. The authors of the studies [85,86] have found that from the point of view of chemical, mineralogical composition and refractoriness, the slags from the production of high-carbon ferrochrome and low-carbon ferrochrome can be a valuable raw material for the manufacture of heat-resistant materials.…”
Section: Leachingmentioning
confidence: 99%
See 1 more Smart Citation
“…In the slag from the production of low-carbon ferrochrome, the main crystalline phase is calcium orthosilicateγ-Ca2SiO4, as well as magnesium orthosilicate (forsterite) Mg2SiO4 [85]. The authors of the studies [85,86] have found that from the point of view of chemical, mineralogical composition and refractoriness, the slags from the production of high-carbon ferrochrome and low-carbon ferrochrome can be a valuable raw material for the manufacture of heat-resistant materials.…”
Section: Leachingmentioning
confidence: 99%
“…Moreover, more than 5 million tons are represented by slags from the production of high-carbon ferrochrome and more than 8 mln. tons -pulverized, low-carbon ferrochrome slag [8]. According to [9] data in Aktobe region, contamination of soil, water and air with hexavalent chromium is recorded with a significant exceedance of the MPC until 2010.…”
Section: Introductionmentioning
confidence: 99%
“…Its non-metallic components form up to 10-12 tonnes of slag per 1 tonne of phosphorus. The slag is a waste product (46-50% of CaO,.0% of Р2O5, 2-3% of CaF2); it is stored in dumps, occupies land, and worsens the ecology of the region due to the dust formation (Bazhirov et al, 1998). There are some methods for processing phosphorus-containing slags and using them for the production of fertilizers (Hou et al, 2021), brick (Kovkov et al, 2009), silicon dioxide (Bochevskaya et al, 2019), cement (Suleimenov et al, 1980), and concrete products (Khudyakova et al, 2009).…”
Section: Introductionmentioning
confidence: 99%
“…There are some methods for processing phosphorus-containing slags and using them for the production of fertilizers (Hou et al, 2021), brick (Kovkov et al, 2009), silicon dioxide (Bochevskaya et al, 2019), cement (Suleimenov et al, 1980), and concrete products (Khudyakova et al, 2009). However, phosphorus slag has a limited demand in the construction industry due to the fact that it contains P2O5 (up to 3%), which forms a poisonous gas -phosphine -in a humid medium (Bazhirov et al, 1998).…”
Section: Introductionmentioning
confidence: 99%
“…The industry producing ceramic building materials is marked by unlimited possibilities for using waste [16,17]. This is due to the large scale and material consumption of the construction complex as well as its range of products.…”
mentioning
confidence: 99%